KESANTUNAN BERBAHASA ANTARA MAHASISWA DAN DOSEN MELALUI MEDIA SOSIAL WHAT’S UP - Helmita Helmita (Universitas Andalas, 2018)
Language politeness is necessary in communicating with one another. By having a polite language in addition to a person's relationship can become better, one's heart also will not be hurt by listening the speech that spoken. This research aims to; 1. Know what kind of speech in conversation between student and lecturer through social media what's up? 2. Knowing the extent to which the utterance is included in positive politeness and negative politeness. The theory used in this research is the theory of politeness from Brown and Levinson. This research is descriptive qualitative. The method used is observation and using the technique of record. Sources of data in this study from social media “What's up”, the conversation taken from May to August 2017. From this study found that sometimes students are not good at placing where the utterance should be spoken with the lecturer and where speech should be spoken with friends. Besides, there is also found that sometimes there are students who seem to dictate or manage the schedule of the lecturer. This is certainly not very polite done especially when in the academic environment. Although there are also other coursework that is polite but this speech is not polite sometimes more do not know the norm. More negative politeness is found than positive politeness in this research data.Key Words: Politeness, Speech Act, Social media, What’s Up